Behavioral economics in the thought of Imam al-Ghazali with reference to the book "Ma'arij al-Quds fi Madarij Ma'rifat al-Nafs" - Bahlaq, Fairouz Ahmad Yousef (Journal of Islamic and Religious Studies, 2025)
The research aims to highlight the psychological economic behaviors stemming from Imam Al-Ghazali's spiritual religious thought and their compatibility with the tenets of modern behavioral economics, which reshapes the classical theory based on maximizing utility and profit and assuming absolute rationality in economic decisions. The research relies on an analysis of Al-Ghazali's book, "Ma'arij Al-Quds fi Madarij Ma'rifat Al-Nafs," to illustrate how psychological and social factors can be integrated into understanding economic behavior, thus offering a vision that bridges the Islamic perspective with behavioral economics. The research addresses three main axes: It begins with Al-Ghazali's intellectual biography, discussing the stages of his scientific development and his most prominent works, with a particular focus on "Ma'arij Al-Quds," in which he analyzed the human psyche and its relationship to decision-making. It then examines the tenets of behavioral economics, defining the concept and its origins, focusing on points such as "bounded rationality," "loss aversion," and "psychological framing." Finally, the applied comparison highlights the similarities between Al-Ghazali's thought (such as the central role of moral values such as asceticism and justice) and the principles of behavioral economics (such as the focus on emotions and social influences in decisions). The study also emphasizes that Al-Ghazali provided a unique framework for understanding economic behavior by linking it to spiritual and moral dimensions, this madehim a forerunner in the study of irrational influences within the field of economics. This study highlights the importance of rereading the Islamic heritage through the lens of modern behavioral sciences to promote sustainable economic policies.